Invasive behavior of mouse sarcoma cells is inhibited by blocking a 37,000-dalton plasma membrane glycoprotein with Fab fragments. - Steinemann, C (1984)
Abercrombie 's confronted explant technique was used to study the role of tumor surface antigens in malignant invasion. Plasma membranes were isolated from mouse sarcoma cells ( FS9 ) and a mouse cell line (L929) of the same H-2 haplotype. FS9 cells are highly invasive when confronted with chicken heart fibroblasts, whereas the L929 cells are not [ Abercrombie , M. (1979) Nature (London) 281, 259-262]. The FS9 plasma membranes contained significantly higher concentrations of a 37,000-dalton glycoprotein. When antiserum directed against FS9 plasma membranes was preabsorbed with L929 cells, the antibodies remaining reacted predominantly with the 37,000-dalton antigen. Fab fragment prepared from the preabsorbed antiserum inhibited the invasion of chicken heart fibroblasts by FS9 cells. Fab prepared from a monoclonal antibody directed against the 37,000-dalton antigen also inhibited invasivity , whereas monoclonal antibodies reacting with two other FS9 cell surface antigens did not. The results imply a relationship between the increased concentration of the 37,000-dalton glycoprotein on the surface of the FS9 cells and their invasivity .